Cruciferous Weed Isolates of Xanthomonas campestris Yield Insight into Pathovar Genomic Relationships and Genetic Determinants of Host and Tissue Specificity - Zoë E. Dubrow; Sara C. D. Carpenter; Morgan E. Carter; Ayress Grinage; Carine Gris; Emmanuelle Lauber; Jules Butchachas; Jonathan M. Jacobs; Christine D. Smart; Matthew A. Tancos; Laurent D. Noël; Adam J. Bogdanove (Molecular Plant-Microbe Interactions, 2022)
Pathovars of Xanthomonas campestris cause distinct diseases on different brassicaceous hosts. The genomic relationships among pathovars as well as the genetic determinants of host range and tissue specificity remain poorly understood despite decades of research. Here, leveraging advances in multiplexed long-read technology, we fully sequenced the genomes of a collection of X. campestris strains isolated from cruciferous crops and weeds in New York and California as well as strains from global collections, to investigate pathovar relationships and candidate genes for host- and tissue-specificity. Pathogenicity assays and genomic comparisons across this collection and publicly available X. campestris genomes revealed a correlation between pathovar and genomic relatedness and provide support for X. campestris pv. barbareae, the validity of which had been questioned. Linking strain host range with type III effector repertoires identified AvrAC (also ‘XopAC’) as a candidate host-range determinant, preventing infection of Matthiola incana, and this was confirmed experimentally. Furthermore, the presence of a copy of the cellobiosidase gene cbsA with coding sequence for a signal peptide was found to correlate with the ability to infect vascular tissues, in agreement with a previous study of diverse Xanthomonas species; however, heterologous expression in strains lacking the gene gave mixed results, indicating that factors in addition to cbsA influence tissue specificity of X. campestris pathovars. [Graphic: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.